Investigation of the self-cleaning properties of cotton fabrics finished with Nano-TiO2 and Nano-TiO2 mixed with fumed silica. - Pisitsak, Penwisa; Samootsoot, Arnon; Chokpanich, Nassarin (Asia-Pacific Journal of Science and Technology, 2017)
The aim of this work is to investigate the self-cleaning properties of woven cotton fabrics after coating with either nanoparticles of TiO2 (Degussa, P-25) or mixtures of P-25 and fumed silica (Aerosil200). The TiO2 and fumed silica were dispersed in toluene by exposure to ultrasound and then stirring prior to use. After drying, the particles were dispersed in water at 0, 0.5, 1.0 and 2.0 wt/wt% then applied to the cotton fabrics using a pad-dry-cure technique. The finished fabrics were stained with direct dye, coffee, tomato sauce, and soft drink, and then irradiated with artificial sunlight (xenon arc lamp) for 24 h. The K/S values at different time intervals were recorded to measure the self-cleaning ability of the finished fabrics. The results showed that every sample possessed self-cleaning abilities. The self-cleaning effect was stronger for samples coated with higher TiO2 concentrations. The decomposition of a direct dye stain was most significant compared to other stains. Mostly, the finished samples appeared clean after one wash whereas the untreated fabrics required repeated washing. However, with the addition of fumed silica, a reduction in self-cleaning ability was observed.